2020
DOI: 10.3390/agronomy10040535
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Responses of Soybean Genotypes to Starter Nitrogen Fertilizer Rate

Abstract: The main nitrogen (N) sources in soybean production originate from soil fixing bacteria Bradyrhizobium spp. and from mineralization of soil organic N. These sources of N are often not sufficient to cover the N needs of the soybean. The present two-year field study aimed to evaluate the effects of soybean genotypes (Valjevka and Galina) and rates of starter fertilizer N (0, 30, 60, and 90 kg ha −1 ) on quantitative and qualitative parameters and on rain use efficiency (RUE) under contrasting weather conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
1
5
0
1
Order By: Relevance
“…Water shortages lead to reduced plant height [36], particularly when they occur at the stage of shoot formation. Newark [37] and El Kheir et al [38] have found that insufficient precipitation at this stage may reduce plant height by about 30% to 70% [39]. In the present work, mean root mass developed by cultivars was lower in 2018 when, in June, precipitation exceeded 70 mm and plants did not have to develop an extensive rooting system to increase water supply from the soil.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Water shortages lead to reduced plant height [36], particularly when they occur at the stage of shoot formation. Newark [37] and El Kheir et al [38] have found that insufficient precipitation at this stage may reduce plant height by about 30% to 70% [39]. In the present work, mean root mass developed by cultivars was lower in 2018 when, in June, precipitation exceeded 70 mm and plants did not have to develop an extensive rooting system to increase water supply from the soil.…”
Section: Discussionsupporting
confidence: 44%
“…It was also observed that soybean plants produced lower seed mass in 2018 than in 2017, which was probably due to high temperatures and insufficient precipitation. Mandić et al [39,43] and Ghassemi-Golezani and Lotfi [44] have found that drought occurring during the reproductive period (July-August) causes seed dieback, reduces seed size, shortens the period of seed fill and, as a result, reduces seed yield. According to Purcell et al [45] and Sinclair et al [46], nitrogen content in plants may decline due to insufficient precipitation (water stress) and increased temperatures, which was also confirmed in the work discussed here.…”
Section: Discussionmentioning
confidence: 99%
“…Starter (row) fertilization increases the soil–fertilizer contact by placing nitrogen in the soil zone with a higher root concentration. This in turn increases the effectiveness of this method of sowing a nutrient [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…These yield components are strongly conditioned by each other, and the maximum yields are achieved when they are optimally balanced, because a change in one component is only to a certain extent compensated by changes in another. The dry stress during summer months in 2017 caused yield loss due to a decrease in the yield component traits, similarly to Mandić et al [20]. Therefore, the recommendation for soybean growers is to sow at the beginning of April, so that the plants can make the most of the available precipitation.…”
Section: Year and Genotype Affected Quantitative And Quality Traitsmentioning
confidence: 91%